Reovirus-Specific Ribonucleic Acid from Polysomes of Infected L Cells - Ward, R. (1972)
Polysomes from reovirus-infected L cells were analyzed. Although all 10 transcription products of the viral genome were represented in polysomes and presumably can be translated, fewer than 10 reovirus-specific polypeptides were detected in infected cells. The 5′-terminal sequence of all species of reovirus ribonucleic acid (RNA) from polysomes was ppGpYp, as previously found for the genome double-stranded RNA and the in vitro single-stranded products of the virion-associated RNA polymerase. RNA isolated from both heavy (>30 ribosomes) and light (5 to 8 ribosomes) polysomes includes similar amounts of large, medium, and small classes of reovirus single-stranded RNA, suggesting that linkage of the genome segments observed in virions may occur at the single-strand stage of RNA replication.